Absolute exponential stability of switching time-delay Lurie systems with the application to switching Hopfield neural networks - Wenxiu Zhao, Wenxiu; Sun, Yuangong (Nonlinear Analysis: Modelling and Control, 2025)
This paper investigates the problem of absolute exponential stability analysis for switching time-delay Lurie system (STDLS) with all modes unstable. By proposing a novel switching time-varying Lyapunov–Razumikhin function, a computable sufficient condition is formulated to guarantee absolute exponential stability of STDLS under mode-dependent range dwell-time (MDRDT) switching. Especially, theoretical results are applied to switching delay Hopfield neural network. Simulations are served to illustrate the developed theory.